Administrasi Pendidikan Islam Berbasis Nilai Al-Qur'an dan Sunnah dalam Meningkatkan Mutu Pendidikan - Nur Yaman; Yadi; Meti Fatimah (TSAQOFAH, 2026)
Educational administration is an important factor in determining the quality of educational provision. However, administrative practices in various educational institutions remain largely influenced by modern paradigms oriented toward organizational efficiency, while studies that comprehensively integrate Islamic values remain relatively limited. This study aims to analyze the concept of educational administration from an Islamic perspective based on the Qur’an, the Prophet’s hadith, and the thoughts of Islamic scholars, as well as to examine its implications for the management of Islamic educational institutions in the contemporary era. The study employed a qualitative approach using a literature review method. Data were obtained from the Qur’an, authentic hadith, classical Islamic texts, scholarly books, and reputable journal articles discussing Islamic educational administration. The data were analyzed using content analysis through the stages of reduction, categorization, interpretation, and conclusion drawing. The results indicate that Islamic educational administration is founded on the principles of tawhid, trustworthiness, justice, consultation, professionalism (itqan), accountability, and ihsan. These principles provide the foundation for all functions of educational administration, including planning, organizing, human resource management, directing, coordinating, supervising, financing, and educational evaluation. Educational administration from an Islamic perspective is oriented not only toward organizational effectiveness but is also regarded as a form of worship aimed at realizing the welfare of the Muslim community and producing individuals who possess faith, knowledge, and noble character. This study affirms that the integration of modern administrative theory and Islamic legal values can provide a conceptual foundation for developing the governance of Islamic educational institutions that is effective, professional, accountable, and imbued with the value of worship.